A sky full of song - Meyer, Susan, 1960- (Union Square Kids, 2023)
In 1905 North Dakota, eleven-year-old Russian immigrant Shoshana is bullied for being Jewish, but after listening to the music of her homeland, she is reminded of the resilience and traditions her people have brought all the way to the prairie.